Соціально-економічна оцінка системи стимулювання праці науково-педагогічних працівників - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д. (Ways to Improve Construction Efficiency, 2012)
The system of incentives academic and teaching staff of higher education institutions to develop their creative potential.